Management of infants born to mothers with SARS-CoV2 infection: a prospective observational study - Chokkiyil Ponnambath Hafis Ibrahim; Fatma Oleks Lobko; Ghalia Abou Alchamat; Waleed Gamal Swilam; Saleema Rasool Wani; Soha Tohamy Said; Stefan Weber; Paul Bosio (BMJ Paediatrics Open)
Objectives To assess the clinical risk of mother-to-infant transmission of SARS-CoV2 and transmission during rooming in and breast feeding in infants born to mothers with COVID-19.Design Prospective observational study.Setting A large tertiary maternal and neonatal care centre based in the UAE.Participants Infants born to mothers diagnosed to have COVID-19 at the time of delivery, born between 1 April and 15 June 2020.Main outcome measures Rate of transmission of SARS-CoV2 from mother to infant (vertical or horizontal) while rooming in and breast feeding in hospital and post discharge and associated morbidity and mortality in the neonatal period.Results 73 infants were born to mothers with COVID-19 at the time of delivery. Two infants tested positive for SARS-CoV2 after birth—one had respiratory symptoms related to other causes and the other infant remained well. 57 of mother–infant dyads who were well enough, roomed in while in hospital and all were breast fed. All surviving infants were followed up by telephone at 2 weeks and 4 weeks (or from the patient record review if still on the Neonatal Intensive Care Unit. Majority of the discharged infants were still rooming in with mothers (95% at 2 weeks, 99% at 4 weeks) and still breast fed (99% at 2 weeks, 99% at 4 weeks). None of the infants developed any significant health issues or developed symptoms attributable to SARS-CoV2.Conclusions The risk of mother-to-infant transmission of SARS-CoV2, vertically or horizontally, in the perinatal period is very low. Breast feeding and rooming in can be practised safely with adequate infection control precautions with negligible clinical risk to the infant.